Biochemical composition of Phleum pratense pollen grains: A review. (August 2021) - Visez, Nicolas; de Nadaï, Patricia; Choël, Marie; Farah, Jinane; Hamzé, Mona; Sénéchal, Hélène; Pauwels, Maxime; Frérot, Hélène; Thibaudon, Michel; Poncet, Pascal
Highlights: Allergens of Phleum pratense pollen are classified in eleven groups from 1 to 13. Allergens from groups 1 and 5 are the major contributors to Phl p pollen allergy. Only one quantitative assessment exists for Phl p 1, 2 and 4 allergen groups. Only 20 % of extractible lipids have been identified and quantified. Only 7–8 % of total proteins have been quantified as group 2 and 5 allergens. Abstract: The Poaceae family is composed of 12, 000 plant species. Some of these species produce highly allergenic anemophilous pollen grains (PGs). Phleum pratense pollen grains (PPPGs) emerged as a model for studies related to grass allergy. The biochemical composition of allergenic PGs has not yet been fully described despite potential health effects of PG constituents other than allergenic proteins. This review brings together the information available in literature aiming at creating a comprehensive picture of the current knowledge about the chemical composition of allergenic PGs from timothy grass. PPPGs have an average diameter between 30–35 μm and the mass of a single PG was reported between 11 and 26 ng. The pollen cytoplasm is filled with two types of pollen cytoplasmic granules (PCGs): the starch granules and the polysaccharide particles (p-particles). Starch granules have a size between 0.6–2.5 μm with an average diameter of 1.1 μm (estimated number of 1000 granules per PG) while p-particles have a size ranging around 0.3 to 0.4 μm (estimated number between 61, 000–230, 000 p-particles per PG). The rupture of PG induces the release of PCGs and the dispersion of allergens in the inhalable fraction of atmospheric aerosol. PPPGs are composed of sporopollenin, sugars, polysaccharides, starch, glycoproteins (including allergens), amino-acids, lipids, flavonoids (including isorhamnetin), various elements (the more abundant being Si, Mg and Ca), phenolic compounds, phytoprostanoids, carotenoids (pigments) metals and adsorbed pollutants. PPPG contains about a hundred different proteins with molecular masses ranging from 10 to 94 kDa, with isoelectric points from 3.5–10.6. Among these proteins, allergens are classified in eleven groups from 1 to 13 with allergens from groups 1 and 5 being the major contributors to Phl p pollen allergy. Major allergen Phl p 5 was quantified in PPPGs by several studies with concentration ranging from 2.7 and 3.5 μg.mg −1 in unpolluted environment. Values for other allergens are scarce in literature; only one quantitative assessment exists for allergen groups Phl p 1, 2 and 4. The extractible lipid fraction of PPPGs is estimated between 1.7–2.2% of the total PG mass. The main chemical families of lipids reported in PPPGs are: alkanes, alkenes, alcohols, saturated and unsaturated fatty acids, di- and tri-hydroxylated fatty acids, aldehydes and sterols. Several lipid compounds with potential adjuvant effects on allergy have been specifically quantified in PPPGs: E2-like prostaglandin (PGE2), B4-like leukotriene (LTB4), unsaturated fatty acids (linoleic and linolenic acids and their hydroxylated derivatives), adenosine, vitamins and phenolic compounds. Some other biochemical characteristics such as NAD(P)H oxidase, protease activity and pollen microbiome were described in the literature. The bioaccessibility in physiological conditions has not been described for most biochemicals transported by allergenic PPPGs. There is also a considerable lack of knowledge about the potential health effects of pollen constituents other than allergens. The variability of pollen composition remains also largely unknown despite its importance for plant reproduction and allergy in an environment characterized by chemical pollution, climate change and loss of biodiversity.